Analysis of occlusal characteristics of identical homozygous twins - Kučević, Esad; Pavlović, Jasna; Poštić, Srdjan; Čutović, Tatjana; Todić, Jelena (Vojnosanitetski pregled, 2018)
Background/Aim. Functionally stable occlusion is characterized by optimal and orthopedic stable position of the condyle, harmonious contact ratio of upper and lower teeth in the final occlusal position of the mandible, optimal relationship of dental arches at the eccentric movement of the lower jaw and stable interocclusal space in physiological position. As there are no ideal order of teeth and absolute intermaxilar harmony nor individually acceptable standards or prototype of functionally optimal occlusion, the aim of this study was to analyze occlusal characteristics of identical twins. Methods. This clinical-epidemiological and functional study involved 30 pairs of identical twins, both males and females, aged 20 to 40 years. The main criterion for the selection of participants was preserved function of orofacial system, as a precondition for application of the Peer Assessment Rating (PAR) index, which is the most reliable tool for diagnosing malocclusion and evaluating occlusal parameters: the distance between the contact points of agonists of front segments of the dental arches, side occlusion of the sagittal, vertical and transversal position, overjet, anterior crossbite, deep and open bite, overbite of incisors and relationship of middle dental arches. Results. Using t-test for independent samples, no significant difference in the values of PAR index, according to gender, was established. The average difference of 0.833 between the twin groups (for male twins: ґ = 7.97, SD = 6.625; for female twins: ґ = 7.13, SD = 5.606) was not statistically significant [t (58) = 0.526; p = 0.601; 95% confidence interval: -2.339–4.005]. Conclusion. The lack of significant differences in occlusal PAR index analysis in both the same and different twin groups, implies the dominance of hereditary factors.